The Role of Community Pharmacists during the Pandemic in the World and in Our Country - HIZAL, ÖZGECAN GÜL; UĞRAŞ DİKMEN , ASİYE (Turkey Health Literacy Journal, 2023)
Pharmacists, who are an important part of the health sector and interact intensively with the society within the scope of changing and developing pharmacy services, have turned into professionals who not only fulfill the duty of meeting the prescribed drugs, but also provide consultancy services to patients and closely follow their treatments by applying pharmaceutical care. During the COVID-19 pandemic, pharmacists have started to assume new roles and responsibilities, as well as continuing their pharmaceutical care and consultancy services at the local and national level. In the COVID-19 pandemic, which is accompanied by the infodemic and false information spreads faster than the truth, pharmacists have ensured that accurate information is delivered to the public from a reliable source, preventing them from worrying and panicking. In this study, the roles and responsibilities of pharmacists in our country and around the world during the pandemic were examined in the light of current literature, and it was aimed to take attention to the importance of the subject.
Keywords: COVID-19 Pandemic, Consultant Role of Pharmacist, Pharmaceutical Care, Pharmacist-Patient Communication